Pengembangan Buku Ajar Materi Kalor dan Perpindahannya Berbasis Augmented Reality untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMP - Hidayat, Aprilia Lulita Nadya; Ahmad, Nur; Ridlo, Zainur Rasyid; Putra, Pramudya Dwi Aristya; Yusmar, Firdha (Jurnal Penelitian Pendidikan IPA, 2024)
The Society 5.0 era necessitates that society address problems by harnessing information technology. Augmented Reality, one of the information technologies utilized in the education sector, presents virtual objects alongside real ones in a three-dimensional format, allowing for observation, interaction, and auditory engagement. Heat and transfer materials can be simulated and applied in the form of 3D objects and animations, facilitating direct student interaction and providing a captivating and distinctive learning experience. The objective of this research is to create an Augmented Reality-based textbook on heat and transfer material to enhance the critical thinking skills of junior high school students. This Research & Development used the ADDIE model including analyze, design, develop, implement and evaluate steps. Based on the results, augmented reality-based textbook is highly valid, practical, and effective in showcasing an improvement in the critical thinking skills of junior high school students, with the observed increase falling within the high category, specifically at 0.71